การพัฒนาอุปกรณ์การวิเคราะห์ฐานกระดาษสำหรับการตรวจวัดแบบเรืองแสงของฟอร์มาลดีไฮด์ - ณัฎฐาภรณ์ ทองวัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Formaldehyde or formalin is known to be a carcinogen by IARC classification and not allowed to use in food according to Food. So that is very necessary to detect harmful formaldehyde with a simple and effective method. In this work, the detection of formaldehyde on a paper-based analytical device by a hydrazinyl naphthylamide-based fluorescent probe (RBNA probe) was developed. The concentration of RBNA probe was first optimized for detection of formaldehyde in solution. 50 μM of RBNA probe gave a good sensitivity and low detection limit (0.545 mg/L). Therefore, 50 μM of RBNA probe was applied on paper-based device for detection of formaldehyde. The homemade fluorescence detection system which used a portable USB 2000+ spectrometer used for detection on paper-based device. Unfortunately, it cannot detect formaldehyde on a paper-based device with 50 μM of RBNA probe. Therefore, a design of the homemade fluorescence detection system was test with Rhodamine B which is a strong fluorescent compound. The design can use to detect Rhodamine B on a paper-based device at high concentration (25-100 mg/L) but cannot detect at low concentration (1.0-10 mg/L). As a result, the homemade fluorescence detection system can use to detect fluorescence on paper-based. Nevertheless, the fluorescence intensity from a paper-based detection formaldehyde with 50 μM of RBNA probe may not high enough to detect by the homemade fluorescence detection system.